Level of self-esteem: Is there any difference among physical, verbal, anti-social, and cyber bullies? - Siti Jaizah Nakman; Nurulwahida Azid; Abdul Hamid Busthami Nur (International Journal of Evaluation and Research in Education (IJERE), 2023)
Bullying is one of the major issues worldwide and is one of the most prevalent school violence. Bullying is a negative behavior toward an individual or group of individuals that are considered weak. Bullying is often associated with self-esteem. Therefore, this study was conducted to identify the influence of students’ tendency to be bullies (physical, verbal, anti-social, and cyber) on self-esteem. This study involved 150 secondary school students in the north of peninsular Malaysia. The study also used the cross-sectional survey method by distributing a set of questionnaires to the respondents. The findings of the study found that students who tend to be bullies for the four categories of bullying, namely physical bullying (ß=0.076, t=3.048, p<0.05), verbal (ß=0.080, t=3.052, p<0.05), anti-social (ß=0.084, t=3.055, p <0.05) and cyber (ß=0.046, t=2.815, p<0.05) had a significant influence on level of self-esteem.